Morphology, growth and genetic variations of sago palm (Metroxylon sagu) seedlings derived from seeds (Biodiversitas Journal of Biological Diversity, 2018)
Riyanto R, Widodo I, Abbas B. 2018. Morphology, growth and genetic variations of sago palm (Metroxylon sagu) seedlings derived from seeds. Biodiversitas 19: 682-688. Propagations of Sago palm using seeds will result in large variations of seedlings due to segregation resulting in the genetic diversity. The objectives of this study are to observe the morphology, growth and genetic variations of sago palm seedlings derived from seeds resulted from natural pollination. Morphological diversities of sago palm seedlings showed in high variations with the similarity coefficient ranging from 10% to 69%. Growth patterns of sago palm seedlings were divided into three categories, i.e., slow, medium, and fast growth. Genetic characters of sago palm seedlings showed that sago palm seedlings were varied with coefficients ranging from 23.6-74.5% and seedlings samples were separated into three groups of 49% the differentiation level. Based on the morphological, growth, and genetic characteristics of sago palm seedlings derived from seeds, it is predicted that sago palms in the natural condition may occur because of cross-pollination.
Keywords: Genetic; morphology; RAPD; sago palm; seedlings